2023
DOI: 10.1186/s12888-023-04946-y
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive awareness in a Norwegian population: psychometric properties of the Multidimensional Assessment of Interoceptive Awareness (MAIA) 2

Abstract: Background Interoception plays a vital role in human cognition and emotion and is an increasingly important part of clinical studies of mind–body approaches and mental health. Interoceptive awareness (IA) encompasses numerous mind–body components and can be assessed by employing a self-report measure such as the Multidimensional Assessment of Interoceptive Awareness (MAIA), which has been adapted and validated across several countries and is used in experimental and clinical settings. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…It is important to note that the gender distribution is not equal and thus does not reflect the gender composition of the general Dutch population. Nevertheless, compared with other studies with much smaller male datasets [e.g., 20 , 21 , 23 , 24 ], this study includes a substantial number of male participants ( n = 331), thus contributing valuable comparative data. It is evident that more data from an elderly group and male respondents need to become available in order to speak not of a convenience sample but of a sample representing the Dutch population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the gender distribution is not equal and thus does not reflect the gender composition of the general Dutch population. Nevertheless, compared with other studies with much smaller male datasets [e.g., 20 , 21 , 23 , 24 ], this study includes a substantial number of male participants ( n = 331), thus contributing valuable comparative data. It is evident that more data from an elderly group and male respondents need to become available in order to speak not of a convenience sample but of a sample representing the Dutch population.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the MAIA-2 is the most used self-report questionnaire, covering different components of interoceptive awareness. The MAIA-2 has been translated and psychometrically evaluated in several languages, including French [ 20 ], Turkish [ 21 ], Chinese [ 22 ], Norwegian [ 23 ], Ukrainian [ 24 ], and German [ 5 ]. These studies used non-clinical samples except for the study conducted by Eggart et al [ 5 ], who provided psychometric values for the MAIA-2 in a group of people with Major Depressive Disorder.…”
Section: Introductionmentioning
confidence: 99%
“…MAIA was used in many previous studies related to contemplative main-body interventions 30 , 31 , 36 , mindfulness 39 , 46 , 49 51 , 53 , physical activity 8 – 11 , 13 , 14 , 24 , 37 , emotional susceptibility 38 , emotion recognition 54 , emotion regulation 49 , alexithymia 29 , 39 , anxiety 27 , 29 , 41 , 46 , 49 , 50 , depression 27 , 28 , 30 , 31 , pain 28 , 32 , 49 , somatization 27 , eating disorders symptoms 27 , 29 , 37 , personality 39 , 41 , 55 , 56 , self-esteem 51 , and well-being 53 . MAIA was validated and adapted to many languages, including Arabic 40 , Chinese 45 , 50 , French 39 , German 33 , 36 , Hungarian 41 , Italian 38 , Japanese 43 , 49 , Korean 44 , Lithuanian 35 Malay 51 , Norwegian 42 , Polish 37 , Portuguese 46 , Spanish 47 , 52 , and Turkish ...…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies examined only multidimensional factor structure (all scales of the MAIA are intercorrelated), some researchers examined higher-order general factors using CFA 39 , 41 , 42 , including hierarchical second-order (selected items are related to specific scales and all eight scales of MAIA are related to the general factor of interoceptive awareness on a higher level) and bi-factor structures (all items of MAIA are related to the general factor, and selected items to eight scales, independently). Fiskum et al 42 confirmed that both second-order and bi-factor models of MAIA-2 have appropriate structure and good fit indices, so the MAIA-2 total score can be considered in further studies as an indicator of a general factor of interoception. However, resolutions of such an approach did not always cover all items and scales of MAIA 39 , 41 , and were far from theoretical assumptions 24 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation